Cognitive Motor Dissociation in Disorders of Consciousness - Bodien, Yelena G.; Allanson, Judith; Cardone, Paolo; Bonhomme, Arthur; Carmona, Jerina; Chatelle, Camille; Chennu, Srivas; Conte, Mary; Dehaene, Stanislas; Finoia, Paola; Heinonen, Gregory; Hersh, Jennifer E.; et al. (The New England journal of medicine, 2024)
Among 241 persons with disorders of consciousness who had no observable response to commands, 25% had a verifiable response to commands on EEG or functional MRI, a condition known as cognitive motor dissociation.